Stress distribution in dental roots restored with different post and core materials - Lopes, Guilherme Da [UNESP]; Freitas, Valéria Da; Matos, Jefferson [UNESP]; Andrade, Valdir; Nishioka, Renato [UNESP]; Casas, Estevam (Wolters Kluwer, 2019)
Aim: The aim of this study was to investigate the stress distribution in models of maxillary central incisors restored with different post and core systems. Materials and Methods: A finite-element model of a maxillary central incisor was simulated in four different configurations-model 1: An intact tooth, Model 2: Received gold cast metallic post and core, Model 3: Received a fiberglass post and core, and Model 4: Had a fiberglass post and the composite resin core. The restored tooth models were assumed to receive a ceramic crown simulating a clinical situation. After the preparation, the geometric models were exported in mesh to the analysis software (ANSYS 10.0, ANSYS Inc., Houston, USA). A 100 N static force at a 130° angle with respect to the longitudinal axis of the tooth was applied to the palatine surface of the model along equally distributed on the element nodes. The values and stress distribution were analyzed. Results: The stress distribution in the radicular structure of the models restored with three different post and core systems was like each other, but the gold cast metallic post and core system slightly improved the pattern of the stress distribution. Conclusions: The placement of post changes the stress distribution behavior, and the material with the highest elastic modulus showed the best performance in the stress distribution.
Keywords: Endodontically treated tooth; Finite-element analysis; Stress distribution